2013
DOI: 10.1371/journal.pone.0080669
|View full text |Cite
|
Sign up to set email alerts
|

Gr1intCD11b+ Myeloid-Derived Suppressor Cells in Mycobacterium tuberculosis Infection

Abstract: BackgroundTuberculosis is one of the world’s leading killers, stealing 1.4 million lives and causing 8.7 million new and relapsed infections in 2011. The only vaccine against tuberculosis is BCG which demonstrates variable efficacy in adults worldwide. Human infection with Mycobacterium tuberculosis results in the influx of inflammatory cells to the lung in an attempt to wall off bacilli by forming a granuloma. Gr1intCD11b+ cells are called myeloid-derived suppressor cells (MDSC) and play a major role in regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
78
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 51 publications
(70 reference statements)
9
78
2
1
Order By: Relevance
“…Our findings agree with previous observations showing increased Arg1 mRNA expression and Arg1 activity over the course of aerosol Mtb infection and its association with augmented bacterial burden in murine lungs (22,26,50). Using the aerosol Mtb challenge of macrophage Arg1-deficient mice, El Kasmi et al (22) demonstrated improved control of Mtb in the lung.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings agree with previous observations showing increased Arg1 mRNA expression and Arg1 activity over the course of aerosol Mtb infection and its association with augmented bacterial burden in murine lungs (22,26,50). Using the aerosol Mtb challenge of macrophage Arg1-deficient mice, El Kasmi et al (22) demonstrated improved control of Mtb in the lung.…”
Section: Discussionsupporting
confidence: 92%
“…As reported in human and NHP TB granulomas (11,38), inflammatory macrophages were the major cellular population expressing Arg1 in TB lung granulomas of Nos2 −/− mice. This observation contrasts with the recent finding that in aerosol Mtb-infected Nos2 −/− mice CD11b + myeloid-derived suppressor cells (MDSCs) expressing high levels of Arg1 are located at the edges of necrotic lung lesions in which neutrophils and MDSCs are thought to be the main drivers of lung necrosis (50). Differences in bacterial burden in the lung upon aerosol and dermal infection would affect the kinetics of inflammatory cellular influx into the lung, which subsequently determines the ultimate architecture and structure of the lesions (37,50).…”
Section: Discussioncontrasting
confidence: 77%
“…4 and 5) were present at higher levels during the chronic stage of murine tuberculosis (43), as were Gr1 int cells, suggesting a Gr1 ϩ myeloid-derived suppressor cell phenotype. Based on previous experiments showing that Gr1 int MDSC cells diminished the T-cell protective responses in a murine TB model (44,45), our results corroborate these findings to a certain degree, particularly because M. tuberculosis-infected animals treated with ERA showed a diminished ability to control the infection. Further, ETR signaling could modulate recruiting or phenotype changes of these MDSC cells.…”
Section: Discussionsupporting
confidence: 88%
“…MDSC-like cells have previously been described during TB disease in susceptible mouse models (24,37) and early during disease in TB patients (38). Both in experimental models and humans, accumulation of MDSCs is associated with increased TB disease severity, and depletion of MDSCs reverses TB disease severity in Mtb-susceptible mice (24,38).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with these studies, our data show that IL-17 depletion results in increased HIF1α-expressing myeloid cells and accumulation of large numbers of MDSCs within TB granulomas, coinciding with increased disease severity and suppression of T cell responses. That MDSCs themselves have been implicated as IL-17 producers during Mtb infection (37) suggests that IL-17 made by MDSCs may be a necessary feedback loop to limit excessive HIF1α production in MDSCs. Interestingly, in a systemic Mycobacterium avium model of infection, mice deficient in HIF1α expression in myeloid cells demonstrated increased liver necrosis (39).…”
Section: Discussionmentioning
confidence: 99%